The Influence of 5% KOH Immersion for Seaweed as Raw Materials for Air Freshener Gel - Dewa, Riardi Pratista; Radiena, Mozes Syukur Yonidar (Biopropal Industri, 2014)
The effect of submersion KOH 5% for seaweed as raw materials products air freshener gel has been studied. Seaweed in Indonesia has a big potentially and it is commonly used in food products, beverages, pharmaceuticals and cosmetics. This research aims to use seaweed as a feedstock gel air freshener. Soaking seaweed with KOH was conducted to determine the nature of the water content and gel strength of the gel air freshener products generated given the scent of oranges and cloves. KOH concentration used was 5%. The results showed the water content of seaweed with KOH soaked lower than without KOH, whereas the gel strength with marinated seaweed KOH higher than without KOH. The results of organoleptic test, in this case the sense of smell, the air freshener gel product indicates that the product that uses citrus scent perfuming/lemon, panelists preferred more than the product is scented gel air freshener clove oil.